Risk modeling in working out the plan of developing the road transport cargo enterprise - Shevchenko, Inna; Dmytriiev, Illia; Dmytriieva, Oksana; Шевченко, Інна Юріївна; Дмитрієв, Ілля Андрійович; Дмитрієва, Оксана Іллівна (Харківський національний автомобільно-дорожній університет, 2022)
Problem. In recent years, there has been a rather stable trend of reorientation of the freight transportation market in Ukraine from the predominant use of rail transport to customers preferring road transport for moving goods. Relying on the indicated trend and the prospect of its preservation in view of the indisputable manoeuvre advantages of road transport in the conditions of martial law, the study of the problematic issues of the development of road transport cargo enterprises, among which the risk modeling of their operational activities occupies a prominent place, becomes relevant. Goal. The purpose of the scientific work is to study the methodological and applied aspects of risk modeling when working out a plan for developing a cargo enterprise of road transport. Methodology. The method of analysis and synthesis, system approach, observation method, comparative analysis, factor analysis method, simulation modeling method, and experimental method were used in the work to study the methodological and applied aspects of risk modeling when elaborating a plan for developing a road transport cargo enterprise. Results. The risk model presented in the study makes it possible to identify the optimal level of risk when elaborating a plan for development of a road transport cargo enterprise based on variants of the key indicator of the volume of cargo transportation (including financial indicators). Originality. In the process of modeling in one cycle, you can get up to 24 different options for the values of the optimal level of risk for the implementation of the plan for development of the road transport cargo enterprise, taking into account the differentiation of the parameters of the risk model, in particular, six options for the distance of cargo transportation and four classes of cargo. Practical value. The proposed methodical approach to risk modeling when working out a plan for developing a road transport cargo enterprise takes into account the probable change in demand for freight transportation, which gives the enterprise the opportunity to quickly respond to changes in market conditions and successfully plan activities in conditions of incomplete certainty, lack of information and the presence of risk.
Моделювання ризику при розробленні плану розвитку вантажного підприємства автомобільного транспорту
Keywords: risk modeling; road transport cargo enterprises; development plan; optimal risk; market demand; моделювання ризику; підприємства вантажного автомобільного транспорту; план розвитку; оптимальний ризик; ринковий попит; 338.3; 629.3; 10.30977/AT.2019-8342.2022.51.0.10